Simultaneous photocatalytic H2 generation and organic synthesis over crystalline–amorphous Pd nanocube decorated Cs3Bi2Br9. Issue 76 (6th September 2022) - Wang, Chunhua; Weng, Bo; Liao, Yuhe; Liu, Biao; Keshavarz, Masoumeh; Ding, Yang; Huang, Haowei; Verhaeghe, Davy; Steele, Julian A.; Feng, Wenhui; Su, Bao-Lian; Hofkens, Johan; et al.
Abstract : Development of metal halide perovskite photocatalysts that can efficiently perform selective organic oxidations in combination with H2 evolution at mild conditions. Abstract : Cs3 Bi2 Br9 decorated with crystalline–amorphous Pd nanocubes as cocatalysts is reported to photocatalytically coproduce ca. 1400 μmol h −1 g −1 of H2 and benzaldehyde from the selective benzyl alcohol oxidation. This route offers an alternative for photocatalytic H2 generation using metal halide perovskites under mild conditions.